Balance-of-payments-constrained growth in Brazil: 1951-2008 - Alencar, Douglas Alcantara; Strachman, Eduardo [UNESP] (M E Sharpe Inc, 2014)
The aim of this study is to determine whether Brazil's economic growth has been constrained by the balance of payments in the long run. The question underpinning the analysis can be expressed as follows: Was economic growth in the period 1951-2008 constrained by the balance of payments? To answer this question, the study employs the externally constrained growth methodology developed by Lima and Carvalho (2009), among others. The main statistical method used is vector error correction. The conclusion is that the rate of economic growth in Brazil was restricted by the external sector in the period concerned, validating the theory of balance-of-payments growth constraint with regard to the economic history of Brazil.
Keywords: economic growth; external constraint; time series